2018
DOI: 10.1186/s13148-018-0561-5
|View full text |Cite
|
Sign up to set email alerts
|

T cell epigenetic remodeling and accelerated epigenetic aging are linked to long-term immune alterations in childhood cancer survivors

Abstract: BackgroundCancer treatments have substantially improved childhood cancer survival but are accompanied by long-term complications, notably chronic inflammatory diseases. We hypothesize that cancer treatments could lead to long-term epigenetic changes in immune cells, resulting in increased prevalence of inflammatory diseases in cancer survivors.ResultsTo test this hypothesis, we established the epigenetic and transcriptomic profiles of immune cells from 44 childhood cancer survivors (CCS, > 16 years old) on ful… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 56 publications
2
39
0
Order By: Relevance
“…reported that, although pediatric patients with neuroblastoma showed features of immunosenescence at early time-points (1–4 years) after treatment, they also began to show signs of immune reconstitution 5 or more years after diagnosis ( 57 ). However, the possibility of premature aging of the immune system at later time-points cannot be excluded and, as already stated, recovery has not been reported in survivors of other cancer types ( 16 , 50 , 49 ).…”
Section: Effect Of Cancer Treatment Regimens On Immunosenescencementioning
confidence: 92%
See 1 more Smart Citation
“…reported that, although pediatric patients with neuroblastoma showed features of immunosenescence at early time-points (1–4 years) after treatment, they also began to show signs of immune reconstitution 5 or more years after diagnosis ( 57 ). However, the possibility of premature aging of the immune system at later time-points cannot be excluded and, as already stated, recovery has not been reported in survivors of other cancer types ( 16 , 50 , 49 ).…”
Section: Effect Of Cancer Treatment Regimens On Immunosenescencementioning
confidence: 92%
“…High-dose chemotherapy combined with autologous stem cell transplantation has been associated with low number of naïve and accumulation of CD28- T-cells, and high expression of senescence markers was detected in CD3+ cells several years after the end of treatment ( 53 , 55 ). Additionally, chemotherapy in combination with total body irradiation and HSCT has been associated with long-term epigenetic alterations of genes responsible for immune/inflammatory processes and oxidative stress ( 16 ). To date, only one paper has described the recovery of the immune system after chemotherapy and HSCT ( 57 ).…”
Section: Effect Of Cancer Treatment Regimens On Immunosenescencementioning
confidence: 99%
“…We recently reported that transcriptomic and epigenetic mechanisms partly decouple in cancer development [72,73] and cell differentiation [50]. Thus, the expression changes observed might reflect changed chromatin organization leading to altered cell function in type 1 compared with type 2 as discussed, e.g., as epigenetic mechanisms accompanying ageing [74] and inflammation [75][76][77][78] and associating with changes of DNA-methylation and histonemarks governing gene activity.…”
Section: Epigenetic Background and Ageing Clocksmentioning
confidence: 99%
“…Next, we analyze the baseline CD8 + T cells using an assay for transposase-accessible chromatin using sequencing (ATAC-seq) 8 to further characterize the epigenetic landscape of circulating CD8 + T cells which may reflect host-tumor interactions. Chronic stress 9 11 caused by factors such as pathogens, microbiota, acidity, hypoxia, glucose deprivation, and the tumor microenvironment can cause epigenetic changes 12 , 13 that lead to subtle to profound alterations in the immune system 14 , 15 . These host-tumor interactions can alter epigenetic characteristics of circulating CD8 + T cells which may increase or decrease response to anti-PD-1 treatment in cancer patients 16 , 17 .…”
Section: Introductionmentioning
confidence: 99%